Defect-state layered ferrous titanate induced methane conversion photocatalyst as well as preparation method and application thereof
The defective layered ferrous titanate nanosheet photocatalyst was prepared through sol-gel technology. Combined with alkali etching hydrothermal method and photo-driven technology, the problem of methane being difficult to activate at room temperature was solved, and high-efficiency methane conversion was achieved, reducing the Energy consumption and improve the cycle stability of the catalyst and product generation rate.
Patent Information
- Application Number
- CN202411375030.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The low polarization rate and high bond of methane make it difficult to activate under normal conditions, resulting in the catalytic conversion requiring harsh reaction conditions, increasing energy consumption and catalyst deactivation. It is difficult for existing photocatalytic technologies to achieve high-efficiency methane conversion at room temperature. .
Using sol-gel technology to prepare defective layered ferrous titanate nanoparticles and nanosheets as photocatalysts, layered structures are synthesized by alkali etching hydrothermal method, and combined with photo-driven technology to perform methane oxygen-free dehydrogenation at room temperature The combined reaction produces ethane and hydrogen.
It achieves efficient methane activation under mild conditions, reduces energy consumption, good catalyst circulation stability, can be reused multiple times, significantly improves the rate of ethane and hydrogen production, and is environmentally friendly and green.
Smart Images

Figure CN119259046A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of methane catalytic conversion, and specifically relates to a photocatalyst for inducing methane conversion by defective layered ferrous titanate, a preparation method and application thereof in photocatalytic dehydrogenation of methane molecules to produce ethane and hydrogen. Background Art
[0002] Since the mid-twentieth century, with the advancement of oil exploration technology and mining methods, the chemical industry using oil as raw material has flourished at an unprecedented rate. Oil is a non-renewable resource with limited reserves. With the increasing shortage of oil resources, it is urgent to find and develop alternative energy sources. Among the many alternatives, natural gas has a high application prospect due to its many unique properties. Natural gas reserves are huge. It is the main component of resources such as coalbed methane, biogas, shale gas, and combustible ice, and plays an irreplaceable energy role in human society. In 2021, natural gas accounted for 24.4% of the world's total energy production. In the past 20 years, global natural gas production has increased from 2523.9 billion cubic meters to 4036.9 billion cubic meters, an increase of about 60%. Compared with oil and coal, natural gas releases significantly less sulfur oxide and nitrogen oxide pollutants when burned, and its calorific value is also higher, so it is considered the cleanest fossil energy.
[0003] From a global perspective, the development of chemical synthesis using natural gas as raw materials has become a prominent research hotspot. It is foreseeable that in the near future, the chemical industry will enter an era of rapid development with natural gas as the core. With the continuous increase in proven reserves of natural gas, methane, as the main component of natural gas (wt>80%), has the highest H / C ratio among hydrocarbons and is an important raw material for the preparation of hydrogen and multi-carbon products, rather than just as a fuel, which has attracted widespread attention. This shift provides an opportunity to reduce the current chemical industry's heavy dependence on increasingly depleted crude oil.
[0004] Catalytic methane conversion is an important means to achieve the conversion of methane into valuable chemicals. However, the methane molecule is composed of four identical CH bonds connected by sp 3 The hybridization forms a tetrahedral symmetric structure, in which the bond energy of the CH bond is as high as 435 kJ·mol -1 , and there are neither π bonds nor non-bonding electron pairs in the molecule, and there are no functional groups that are conducive to bond breaking, making it difficult for nucleophilic or electrophilic reactions to occur. -40 C 2 m 2 J -1) makes it difficult to polarize methane under normal local electric fields. Methane conversion often requires harsh reaction conditions to activate methane, resulting in energy consumption, catalyst deactivation and side reactions. For example, Ni-Mo nanocatalysts on single crystal MgO are used for thermal catalytic methane dry reforming, but at 800°C, Ni-Mo nanocatalysts are uncontrollable agglomeration. In addition, large-scale industrial applications have been achieved through steam methane reforming, and the resulting synthesis gas is subsequently used in large quantities for the synthesis of methanol, light olefins and liquid hydrocarbons. However, this conversion route relies on high temperature and high pressure, which increases the complexity and energy consumption of the process. Direct conversion of methane under mild conditions has become an ideal goal for scientific researchers.
[0005] Photocatalysis is a promising alternative that uses photons to drive chemical reactions, mainly at room temperature. Compared with thermocatalysis, photocatalysis produces high-energy charge carriers in methane conversion, which can pre-activate methane and reduce the activation energy. This pre-activation process allows thermodynamically unfavorable reactions to occur even at room temperature, overcoming the obstacles of traditional thermocatalysis. The mechanism of the photocatalytic methane conversion reaction is: the excited state (photogenerated electron-hole separation) entered by the photocatalyst material after absorbing photons interacts with the charge transfer between adsorbed methane molecules, causing the methane molecule to lose or gain an electron, thereby entering a higher energy excited state and inducing further reactions of the methane molecule. Compared with traditional thermocatalytic reactions, photocatalytic reactions start from the high-energy excited state of methane, and can achieve many conversion processes that cannot be carried out spontaneously under traditional ground state conditions (such as the oxygen-free dehydrogenation coupling reaction of methane) or reduce the temperature required for catalytic reactions (such as the oxygen-free aromatization reaction of methane). Wang et al. published a paper titled "Stable solid solution photoinduced non-oxidative coupling of methane" in Angew.Chem.Int.Ed. (Issue 38, 2021, pp. 20760-20764); and published a paper titled "Preparation of stepped CeO2 nanoislands for efficient photocatalytic methane coupling" in ACS Catal. (Issue 17, 2023, pp. 11666-11674). In their research, they found that coordination unsaturation, variable valence state of the central metal, semiconductor polarity, acidic and basic surface, and structural defects are important influencing factors for the photocatalytic conversion of methane. Based on this, catalysts can be scientifically and rationally designed to achieve efficient photocatalytic dehydrogenation coupling of methane. Summary of the invention
[0006] The invention aims to provide a defective layered ferrous titanate induced methane conversion photocatalyst, a preparation method and application thereof in a light-driven methane molecule dehydrogenation coupling reaction under room temperature conditions.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] The preparation method of a defective layered ferrous titanate photocatalyst described in the present invention comprises the following steps:
[0009] (1) Ferrous titanate nanoparticles (FeTiO 3-x -NP): The raw materials are titanium precursor and iron precursor, and FeTiO3 nanoparticles are prepared by sol-gel technology; first, a certain amount of titanium precursor is added to 10mL solvent, and magnetic stirring is performed for 10 to 15 minutes to form solution A; a certain amount of iron precursor is weighed and dissolved in 10mL solvent, and stirred for 10 to 15 minutes to form solution B; solution B is slowly added to solution A so that the molar ratio of Fe ions to Ti ions is 1:1, and then vigorously stirred for 50 to 70 minutes to mix them evenly; a precipitant is then slowly added to the mixed solution until a gel is formed, the gel is allowed to stand overnight for aging, and then dried in an oven at 333 to 373K to obtain an orange-red iron-titanium bimetallic oxide precursor; finally, the precursor is placed in a reducing atmosphere (5% vol H2, 95% vol Ar) at a temperature of 1.5-3.0 K / min to 773-1173 K, and maintained for 1.5-3.0 h to obtain ferrous titanate nanoparticles, which were then washed with deionized water and then dried in an oven at 333-373 K;
[0010] The titanium precursor is one of tetrabutyl titanate, titanium tetrafluoride, titanium trichloride, titanium acetylacetonate, and titanium tetraisopropoxide; the iron precursor is one of ferric nitrate, ferric chloride, and ferric sulfate; the precipitant is ammonia water; the solvent is one of anhydrous methanol, anhydrous ethanol, anhydrous ethylene glycol, and ethylene glycol monomethyl ether;
[0011] (2) Layered ferrous titanate nanosheets (Fe l-x TiO 3-x Preparation of a ferrous titanate (NS) catalyst: synthesizing layered ferrous titanate nanosheets by an alkali etching hydrothermal method; dispersing 50 to 200 mg of the ferrous titanate nanoparticles obtained in step (1) in 30 to 50 mL of a 10 to 20 M alkali solution to form a suspension, and ultrasonically stirring for 0.5 to 2.0 h; then transferring the suspension to a 50 to 100 mL Teflon-lined reactor, and subjecting the reactor to a hydrothermal reaction at 393 to 493 K for 2 to 36 h; after cooling to room temperature, centrifuging the product and washing it with distilled water for several times until the pH value of the filtrate is 7; and finally drying it in a vacuum drying oven to obtain layered ferrous titanate nanosheets (Fe 2O 4 ). l- x TiO 3-x -NS) catalyst, that is, the defective layered ferrous titanate induced methane conversion photocatalyst;
[0012] The alkaline solution is one of sodium hydroxide and potassium hydroxide;
[0013] (3) Photocatalytic methane conversion: Layered ferrous titanate nanosheets (Fe l-x TiO 3-x -NS) catalyst is evenly dispersed at a concentration of 1-5 mg / mL, and then spin-coated on a glass fiber membrane, and maintained at 333-363 K for 10-30 min to volatilize the solvent, to obtain a catalyst with a uniform and flat surface; the obtained catalyst is placed in a quartz reactor, and then activated at a vacuum (<1 Pa) and 473-573 K for 1.5-3.0 h to remove impurities adsorbed on the catalyst surface, and after cooling to room temperature, the catalyst is used for the photocatalytic methane oxygen-free dehydrogenation coupling reaction (methane is the only reactant) at a relatively low temperature (273-353 K) and a relatively low pressure (10-1000 mbar). , is the dehydrogenation coupling under the catalysis of defective layered ferrous titanate to produce ethane and propane with high selectivity, the main reaction is: 2CH4→C2H6+H2; the side reaction is 3CH4→C3H8+2H2; during the catalytic reaction, the catalyst is not consumed and can be recycled many times); the wavelength range of the photocatalytic light source is 200-780nm, and the photocatalytic time is 5-600min; during the photocatalytic reaction, the temperature is controlled by a constant temperature reaction bath; after the reaction is completed, 1mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of hydrogen in the post-reaction quartz reactor is determined by gas chromatography (GC), and the standard curve ( Figure 6 (a) Calculate the generation rate of hydrogen; extract 1 mL of the reaction gas with a gas-tight needle, and use GC to measure the peak area of various hydrocarbons in the quartz reactor after the reaction. Figure 6 (cd)) calculates the production rate of ethane and by-product propane. The calculation formula is as follows:
[0014]
[0015] *Generation rate unit: μmol·g -1 ·h -1 , molar amount unit is μmol, catalyst mass unit is g, reaction time unit is h.
[0016] The invention is based on the construction of defective catalysts based on layered ferrous titanate for the oxygen-free dehydrogenation coupling reaction of methane. Light-driven activation of methane is green, environmentally friendly, cheap and convenient. Designing and constructing nanocatalysts and modifying the catalysts can achieve efficient methane activation under mild conditions, while reducing energy consumption and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 :For the synthesis of ferrous titanate nanoparticles (FeTiO 3-x -NP) and ferrous titanate nanosheets (Fe l-x TiO 3-x-NS) and the standard PDF card of ferrous titanate, indicating that the synthesized product is pure ferrous titanate.
[0018] Figure 2 :(a) is the ferrous titanate nanoparticles (FeTiO 3-x -NP) and high-resolution transmission electron microscopy (HR-TEM) images, with a scale of 2 nm, showing that ferrous titanate mainly exposes two crystal planes with a {012} lattice spacing of The lattice spacing of {104} is (b) Ferrous titanate nanoparticles (FeTiO 3-x -NP) X-ray energy spectrum (EDX) diagram, it is observed that Fe, Ti, and O elements are uniformly distributed in the sample. (c) Particle size distribution diagram of ferrous titanate nanoparticles, the sample particle size is mainly between 20 and 60nm, of which 40nm accounts for a large proportion. Corresponding Example 4
[0019] Figure 3 :(a) Ferrous titanate nanosheets (Fe l-x TiO 3-x -NS) scanning electron microscope photos and high-resolution transmission electron microscope photos show that the sample is mainly layered sheets with a layer spacing of The main exposed crystal planes are {012} planes with a spacing of (b) Ferrous titanate nanosheets (Fe l-x TiO 3-x -NS) X-ray energy spectrum (EDX) diagram, indicating that Fe, Ti, O elements are uniformly distributed. Corresponding Example 4
[0020] Figure 4 :Fe titanate nanosheets (Fe l-x TiO 3-x -NS) at room temperature. The bottom curve represents the catalyst measured under dark conditions, the middle curve is the sample measured after light excitation, and the top curve represents the sample after light excitation and methane reaction. It can be seen that light excitation can produce strong Fe 3+ After the introduction of methane, the signal weakened, indicating that the methane reaction was involved.
[0021] Figure 5 :Fe titanate nanosheets (Fe l-x TiO 3-x-NS) low-temperature electron paramagnetic resonance spectrum (EPR), the bottom curve represents the catalyst measured under dark conditions, the middle curve is the sample after light excitation, and the upper curve represents the sample after light excitation and methane reaction. It can be seen that light excitation can produce enhanced oxygen vacancy signals and generate Ti 3+ After the introduction of methane, the signal weakened, indicating that the reaction of methane was involved.
[0022] Corresponding Example 4
[0023] Figure 6 :(a) is the standard curve of hydrogen gas for measuring the amount of different substances by GC;
[0024] The curve equation is y=1.42x, where y represents the peak area of hydrogen measured by GC on the chromatogram, and x represents the amount of hydrogen introduced, in μmol. This standard curve selects five different amounts of hydrogen, introduces them into a 90mL sealed quartz reactor, extracts 1mL of gas with a gas-tight needle, and injects it into the chromatogram to measure the corresponding peak area, thereby obtaining a standard curve of hydrogen peak area-hydrogen concentration;
[0025] Figure 6 : (b) is a methane standard curve for determining the amount of different substances using GC;
[0026] The curve equation is y=1.51x, where y represents the peak area of methane on the chromatogram measured by GC, and x represents the amount of substance introduced into the methane, in μmol. The standard curve selects five different amounts of methane gas, which are introduced into a 90mL closed quartz reactor, and 1mL of gas is extracted with a gas-tight needle in turn, and the corresponding peak area is measured by injecting it into the chromatogram, thereby obtaining a standard curve of methane peak area-methane concentration; the standard curve mainly calculates the consumption of methane in the reaction and verifies the carbon balance in the reaction.
[0027] Figure 6 :(c) is the ethane standard curve for determining the amount of different substances using GC;
[0028] The curve equation is y=2.82x, where y represents the peak area of ethane measured by GC on the chromatogram, and x represents the amount of ethane introduced, in μmol. This standard curve selects five different amounts of ethane gas, introduces them into a 90mL sealed quartz reactor, extracts 1mL of gas with a gas-tight needle, and injects it into the chromatogram to measure the corresponding peak area, thereby obtaining a standard curve of ethane peak area-ethane concentration;
[0029] Figure 6 : (d) is the propane standard curve for determining the amount of different substances using GC
[0030] The curve equation is y=6.88x, where y represents the peak area of propane measured by GC on the chromatogram, and x represents the amount of propane introduced, in μmol. This standard curve selects five different amounts of propane gas, which are introduced into a 90mL sealed quartz reactor, and 1mL of gas is extracted with a gas-tight needle in turn, and the corresponding peak area is measured by injecting it into the chromatogram, thereby obtaining a standard curve of propane peak area-propane concentration;
[0031] Figure 7 :Photocatalytic performance of different catalysts, the horizontal axis represents different catalysts, and the vertical axis represents the rate of product generation. Ferrous titanate nanoparticles (FeTiO 3-x -NP), ferrous titanate nanosheets (Fe l-x TiO 3-x -NS), and commercially available ferrous titanate (c-FeTiO3, Aladdin), each catalyst corresponds to 2 columns, the left solid column corresponds to the left ordinate, indicating the production rate of the product (ethane, propane); the right slash column corresponds to the right ordinate, indicating the production rate of the product hydrogen. This figure illustrates the ferrous titanate nanosheets (Fe l-x TiO 3-x -NS) has the highest ethane production rate.
[0032] Figure 8 :(a) The reaction rate of methane dehydrogenation coupling catalyzed by samples treated with hydrothermal alkaline etching at different temperatures, corresponding to examples 1 to 6. The horizontal axis represents the catalysts treated with different hydrothermal temperatures, and the vertical axis represents the product generation rate. Each catalyst corresponds to two columns, the left column corresponds to the generation rate of ethane and propane, and the right column corresponds to the generation rate of hydrogen. The figure shows that the sample hydrothermally treated at 453K has the highest production rate, and the generation rate of the product is not much different from the generation rate of hydrogen (2CH4→C2H6+H2). (b) The reaction rate of methane dehydrogenation coupling catalyzed by samples hydrothermally treated at 453K for different times, corresponding to examples 7 to 11, the horizontal axis represents the catalysts treated with different hydrothermal times, and the vertical axis represents the product generation rate. Each catalyst corresponds to two columns, the left column corresponds to the generation rate of ethane and propane, and the right column corresponds to the generation rate of hydrogen. It shows that the sample treated for 12h has the highest production rate. This figure shows that ferrous titanate nanoparticles (FeTiO 3-x The ferrous titanate nanosheets (Fe-NP) were obtained by treating them at 453K for 12h. l-x TiO 3-x -NS) had the highest ethane production rate.
[0033] Fig. 9 :Fe titanate nanosheets (Fe l-x TiO 3-x-NS) catalyzed methane dehydrogenation coupling reaction, corresponding to Example 12. The horizontal axis is the number of cycles, the left vertical axis represents the rate of product generation; the right vertical axis represents the selectivity of ethane in the product. Each cycle corresponds to a column and a point, the column represents the rate of product (ethane, propane), and the point represents the selectivity of ethane in the product. This figure illustrates the Fe l-x TiO 3-x -NS catalyst has good cycle stability and can be reused many times. After 23 cycles of 46 hours, it can still maintain the catalytic effect of the first cycle. DETAILED DESCRIPTION
[0034] Example 1: Preparation method of ferrous titanate nanoparticles treated at different hydrothermal temperatures and application thereof in photocatalytic methane anaerobic coupling reaction.
[0035] (1) Ferrous titanate nanoparticles (FeTiO 3-x Preparation of FeTiO3-NP: The raw materials are ferric nitrate (Fe(NO3)3·9H2O), tetrabutyl titanate, anhydrous ethanol and ammonia water. FeTiO3 nanoparticles were prepared by sol-gel technology. First, 5mL of tetrabutyl titanate (TBT) was added to 10mL of anhydrous ethanol and stirred on a magnetic stirrer for 10min to form solution A. A certain amount of Fe(NO3)3·9H2O 5.94g was weighed and dissolved in 10mL of anhydrous ethanol and stirred for 10min to form solution B. Solution B was slowly added to solution A, with the molar ratio of Fe ions to Ti ions being 1:1, and then vigorously stirred for 1h to mix them evenly. Then ammonia water was slowly added to the mixed solution until a gel was formed. The gel was aged overnight and then dried in a 353K oven to obtain an orange-red iron-titanium bimetallic oxide precursor. Then, the temperature was raised to 773K at 2K / min in a reducing atmosphere (5% vol H2, 95% vol Ar) and maintained for 2 h to obtain ferrous titanate nanoparticles (2.43 g). The nanoparticles were then washed with deionized water and dried in an oven at 353K.
[0036] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was transferred to a 50 mL Teflon-lined reactor and reacted at 393 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0037] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 150.45 μmol·g -1 ·h -1 The generation rate of hydrogen is 183.80 μmol·g -1 ·h -1 , the production rate of propane is 7.43 μmol·g -1 ·h -1 .
[0038] Example 2: Preparation method of ferrous titanate nanoparticles treated at different hydrothermal temperatures and application thereof in photocatalytic methane anaerobic coupling reaction.
[0039] (1) Same as step (1) of Example 1;
[0040] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 413 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0041] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 235.97 μmol·g -1 ·h -1 The generation rate of hydrogen is 261.51 μmol·g -1 ·h -1 , the production rate of propane is 11.68 μmol·g -1 ·h -1 .
[0042] Example 3: Preparation method of ferrous titanate nanoparticles treated at different hydrothermal temperatures and application thereof in photocatalytic methane anaerobic coupling reaction.
[0043] (1) Same as step (1) of Example 1;
[0044] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 433 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0045] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 246.38 μmol·g -1 ·h -1 The generation rate of hydrogen is 272.65 μmol·g -1 ·h -1 , the production rate of propane is 12.21 μmol·g -1 ·h -1 .
[0046] Example 4: Preparation method of ferrous titanate nanoparticles treated at different hydrothermal temperatures and application thereof in photocatalytic methane anaerobic coupling reaction.
[0047] (1) Same as step (1) of Example 1;
[0048] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0049] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 min, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1 Pa), and then increase the temperature to 573 K at 10 K / min for 2 h to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05 MPa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293 K. Use a 300 W xenon lamp (wavelength range is 200-780 nm, CEL-HXUV300, China Education Jinyuan) to perform photocatalytic methane oxygen-free coupling to produce ethane and hydrogen. The illumination time is 2 h. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 301.15 μmol·g -1 ·h -1 The generation rate of hydrogen is 334.48 μmol·g -1 ·h -1 , the production rate of propane is 13.26 μmol·g -1 ·h -1 .
[0050] Example 5: Preparation method of ferrous titanate nanoparticles treated at different hydrothermal temperatures and application thereof in photocatalytic methane anaerobic coupling reaction.
[0051] (1) Same as step (1) of Example 1;
[0052] (2) 10 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 473 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0053] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 183.42 μmol·g -1 ·h -1 The generation rate of hydrogen is 194.80 μmol·g -1 ·h -1 , the production rate of propane is 5.31 μmol·g -1 ·h -1 .
[0054] Example 6: Preparation method of ferrous titanate nanoparticles treated at different hydrothermal temperatures and application thereof in photocatalytic methane anaerobic coupling reaction.
[0055] (1) Same as step (1) of Example 1;
[0056] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 493 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0057] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the ethane production rate can reach 153.67 μmol·g -1 ·h -1 The generation rate of hydrogen is 168.23 μmol·g -1 ·h -1 , the production rate of propane is 6.37 μmol·g -1 ·h -1 .
[0058] Example 7: Preparation method of ferrous titanate nanoparticles treated with different hydrothermal times and application thereof in photocatalytic methane anaerobic coupling reaction.
[0059] (1) Same as step (1) of Example 1;
[0060] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 2 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0061] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the ethane production rate can reach 195.32 μmol·g -1 ·h -1 The generation rate of hydrogen is 242.84 μmol·g -1 ·h -1 , the production rate of propane is 7.43 μmol·g -1 ·h -1 .
[0062] Example 8: Preparation method of ferrous titanate nanoparticles treated with different hydrothermal times and application thereof in photocatalytic methane anaerobic coupling reaction.
[0063] (1) Same as step (1) of Example 1;
[0064] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 4 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0065] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 210.68 μmol·g -1 ·h -1 The generation rate of hydrogen is 266.88 μmol·g -1 ·h -1 , the production rate of propane is 7.43 μmol·g -1 ·h -1 .
[0066] Example 9: Preparation method of ferrous titanate nanoparticles treated with different hydrothermal times and application thereof in photocatalytic methane anaerobic coupling reaction.
[0067] (1) Same as step (1) of Example 1;
[0068] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 8 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0069] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 257.28 μmol·g -1 ·h -1 The generation rate of hydrogen is 301.42 μmol·g -1 ·h -1 , the production rate of propane is 11.15 μmol·g -1 ·h -1 .
[0070] Example 10: Preparation method of ferrous titanate nanoparticles treated with different hydrothermal times and application thereof in photocatalytic methane anaerobic coupling reaction.
[0071] (1) Same as step (1) of Example 1;
[0072] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 24 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0073] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 241.42 μmol·g -1 ·h -1 The generation rate of hydrogen is 266.15 μmol·g -1 ·h -1 , the production rate of propane is 10.08 μmol·g -1 ·h -1 .
[0074] Example 11: Preparation method of ferrous titanate nanoparticles treated with different hydrothermal times and application thereof in photocatalytic methane anaerobic coupling reaction.
[0075] (1) Same as step (1) of Example 1;
[0076] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 36 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0077] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 min, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1 Pa), and then increase the temperature to 573 K at 10 K / min for 2 h to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05 MPa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293 K. Use a 300 W xenon lamp (wavelength range is 200-780 nm, CEL-HXUV300, China Education Jinyuan) to perform photocatalytic methane oxygen-free coupling to produce ethane and hydrogen. The illumination time is 2 h. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the ethane production rate can reach 178.96 μmol·g -1 ·h -1 The generation rate of hydrogen is 186.24 μmol·g -1 ·h -1 , the production rate of propane is 7.43 μmol·g -1 ·h -1 .
[0078] Example 12: Preparation method of hydrothermally treated ferrous titanate nanoparticles and application thereof in photocatalytic methane anaerobic coupling reaction.
[0079] (1) Same as step (1) of Example 1;
[0080] (2) 100 mg of ferrous titanate nanoparticles were dispersed in 30 mL of 10 M NaOH solution to form a suspension. After ultrasonic treatment and stirring for 1 hour, the suspension was then transferred to a 50 mL Teflon-lined reactor and reacted at 453 K for 12 hours. After cooling to room temperature, the product was centrifuged and washed with distilled water several times until the pH value of the filtrate was 7, and then dried in a vacuum drying oven to obtain a 100 mg sample.
[0081] (3) Weigh 10 mg of the catalyst into a 10 mL beaker, disperse it evenly with 5 mL of deionized water, and then spin-coat it on a glass fiber membrane (Shanghai Xingya Purification Material Factory), place it under an infrared lamp and dry it for 30 minutes, and finally obtain a catalyst with a uniform surface. Put the catalyst into a self-made intermittent quartz reactor, place the reactor in an electric heating furnace, connect the vacuum system to evacuate to (<1Pa), and then heat it to 573K at 10K / min for 2 hours to remove water and other gases adsorbed on the catalyst surface. After cooling to room temperature, inject 0.05Mpa of high-purity methane gas (99.999%) into the quartz reactor, and then transfer the reactor to a bath with a constant temperature of 293K, and use a 300W xenon lamp (wavelength range is 200-780nm, Zhongjiao Jinyuan CEL-HXUV300) to perform photocatalytic methane oxygen-free coupling to ethane and hydrogen. The illumination time is 2 hours. After the reaction is completed, the reaction products are quantitatively analyzed using gas chromatography. 1 mL of the gas after the reaction was extracted with a gas-tight needle, and the peak area of hydrogen in the quartz reactor after the reaction was determined by GC. Figure 6 (a)), the molar amount of hydrogen produced can be directly read out, and the molar amount of hydrogen produced divided by the catalytic reaction time and the mass of the catalyst can be used to obtain the hydrogen generation rate; 1 mL of the post-reaction gas is extracted with a gas-tight needle, and the peak area of methane and other hydrocarbons in the quartz reactor after the reaction is determined by GC, and the standard curve ( Figure 6 (cd) Calculate the molar amount of ethane and propane produced. The calculation shows that the production rate of ethane can reach 301.15 μmol·g -1 ·h -1 The generation rate of hydrogen is 334.48 μmol·g -1 ·h -1 , the production rate of propane is 13.26 μmol·g -1 ·h -1 .
[0082] Then the quartz reactor with the catalyst was evacuated again, desorbed, and then 0.05Mpa high-purity methane gas was introduced into the quartz reactor, and then it was placed in a water bath and irradiated with Xe light for 2 hours. The reaction product was then detected by chromatography. The above operation was repeated 23 times, and no significant decrease in activity was observed.
[0083] The above facts show that defective layered ferrous titanate nanosheets have good photocatalytic activity, can efficiently catalyze methane dehydrogenation coupling at room temperature, and the catalyst has good cyclic stability and good selectivity and can be reused many times.
Claims
1. A method for preparing a defective layered ferrous titanate photocatalyst, the steps of which are as follows: (1) Preparation of ferrous titanate nanoparticles: First, a certain amount of titanium precursor is weighed and added to a solvent, and magnetically stirred for 10 to 15 minutes to form a solution A; a certain amount of iron precursor is weighed and dissolved in a solvent, and stirred for 10 to 15 minutes to form a solution B; the solution B is slowly added to the solution A so that the molar ratio of Fe ions to Ti ions is 1:1, and then vigorously stirred for 50 to 70 minutes to mix them evenly; then a precipitant is slowly added to the mixed solution until a gel is formed, the gel is allowed to stand overnight for aging, and then placed in an oven at 333 to 373K to dry, to obtain an orange-red iron-titanium bimetallic oxide precursor; finally, the precursor is heated to 773 to 1173K at 1.5 to 3.0K / min in a reducing atmosphere, and maintained for 1.5 to 3.0 hours to obtain ferrous titanate nanoparticles, which are then washed with deionized water and dried in an oven at 333 to 373K; (2) Preparation of layered ferrous titanate nanosheet catalyst: 50-200 mg of ferrous titanate nanoparticles obtained in step (1) are dispersed in 30-50 mL of a 10-20 M alkaline solution to form a suspension, and ultrasonically stirred for 0.5-2.0 h; the suspension is then transferred to a reactor and subjected to a hydrothermal reaction at 393-493 K for 2-36 h; after cooling to room temperature, the product is centrifuged and washed with distilled water for multiple times until the pH value of the filtrate is 7; and finally dried in a vacuum drying oven to obtain a layered ferrous titanate nanosheet catalyst, i.e., the defective layered ferrous titanate-induced methane conversion photocatalyst; 2. The method for preparing a defective layered ferrous titanate photocatalyst according to claim 1, characterized in that: In step (1), the titanium precursor is one of tetrabutyl titanate, titanium tetrafluoride, titanium trichloride, titanium acetylacetonate, and titanium tetraisopropoxide; the iron precursor is one of ferric nitrate, ferric chloride, and ferric sulfate; the precipitant is ammonia water; and the solvent is one of anhydrous methanol, anhydrous ethanol, anhydrous ethylene glycol, and ethylene glycol monomethyl ether.
3. The method for preparing a defective layered ferrous titanate photocatalyst according to claim 1, characterized in that: The reducing atmosphere in step (1) is a mixture of 5% vol H2 and 95% vol Ar.
4. The method for preparing a defective layered ferrous titanate photocatalyst according to claim 1, characterized in that: In step (2), the alkaline solution is one of sodium hydroxide and potassium hydroxide.
5. A defective layered ferrous titanate photocatalyst, characterized in that: The method is prepared by any one of claims 1 to 4.
6. Use of a defective layered ferrous titanate photocatalyst as claimed in claim 5 in photocatalytic dehydrogenation of methane molecules to produce ethane and hydrogen.
7. The use of a defective layered ferrous titanate photocatalyst as claimed in claim 6 in the photocatalytic dehydrogenation of methane molecules to produce ethane and hydrogen, characterized in that: The method comprises the following steps: uniformly dispersing a layered ferrous titanate nanosheet catalyst with a solvent to a concentration of 1 to 5 mg / mL, and then spin-coating the catalyst on a glass fiber membrane, and maintaining the catalyst at 333 to 363 K for 10 to 30 minutes to volatilize the solvent to obtain a catalyst with a uniform and smooth surface; placing the obtained catalyst in a quartz reactor, and then activating the catalyst at <1 Pa and 473 to 573 K for 1.5 to 3.0 hours to remove impurities adsorbed on the catalyst surface, and after cooling the catalyst to room temperature, using the catalyst for a photocatalytic methane oxygen-free dehydrogenation coupling reaction at 273 to 353 K and 10 to 1000 mbar.
8. The use of a defective layered ferrous titanate photocatalyst as claimed in claim 7 in the photocatalytic dehydrogenation of methane molecules to produce ethane and hydrogen, characterized in that: The wavelength range of the photocatalytic light source is 200-780nm, and the photocatalytic time is 5-600min; during the photocatalytic reaction, the temperature is controlled by a constant temperature reaction bath.
9. The use of a defective layered ferrous titanate photocatalyst as claimed in claim 7 in the photocatalytic dehydrogenation of methane molecules to produce ethane and hydrogen, characterized in that: The solvent is anhydrous ethanol, acetone or deionized water.
Citation Information
Patent Citations
Preparation and application of TiO2@MoS2 composite
CN105148947A
Composite bismuth ferrite photocatalyst and preparation method and application thereof
CN106807400A
Preparation method of P-N heterojunction composite catalyst and product and application
CN109746021A